2010
DOI: 10.1038/nature08977
|View full text |Cite
|
Sign up to set email alerts
|

Cell signalling by microRNA165/6 directs gene dose-dependent root cell fate

Abstract: A key question in developmental biology is how cells exchange positional information for proper patterning during organ development. In plant roots the radial tissue organization is highly conserved with a central vascular cylinder in which two water conducting cell types, protoxylem and metaxylem, are patterned centripetally. We show that this patterning occurs through crosstalk between the vascular cylinder and the surrounding endodermis mediated by cell-to-cell movement of a transcription factor in one dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

27
850
1
7

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 764 publications
(885 citation statements)
references
References 40 publications
27
850
1
7
Order By: Relevance
“…For example, miRNAs have been shown to be key regulators for the induction or maintenance of cell fate in plants (Carlsbecker et al 2010), mammalian cells (Cardinali et al 2009), cancer , and stem cells (Gunaratne 2009;Gangaraju and Lin 2009). Furthermore, miRNAs can serve as biomarkers (Baker 2010).…”
mentioning
confidence: 99%
“…For example, miRNAs have been shown to be key regulators for the induction or maintenance of cell fate in plants (Carlsbecker et al 2010), mammalian cells (Cardinali et al 2009), cancer , and stem cells (Gunaratne 2009;Gangaraju and Lin 2009). Furthermore, miRNAs can serve as biomarkers (Baker 2010).…”
mentioning
confidence: 99%
“…Plasmodesmata serve as intercellular conduits for different species of RNA between plant cells, including siRNAs mediating systemic posttranscriptional silencing (1), miRNAs involved in developmental control (2), the infectious genomes of RNA viruses and viroids (3,4), and cellular mRNAs (5,6). Therefore, techniques which permit the sequence-specific, dynamic localisation of RNAs in live cells are a valuable tool to study plasmodesmata function.…”
Section: Introductionmentioning
confidence: 99%
“…In order to direct pattern formation, an initial asymmetry was required; this was supplied through an initial pre-pattern in PIN7 expression. An experimentally defined network of auxin and cytokinin regulation, including the regulation of AHP6 by PHB (Carlsbecker et al, 2010), was not sufficient to recreate the stable domains of gene expression as seen in roots. However, the authors were able to reproduce the observed patterns of gene expression stably by making two changes to this network configuration.…”
Section: A Minimal Molecular Framework For Vascular Patterningmentioning
confidence: 99%
“…The transcription factor SHORT ROOT (SHR) is expressed within the stele and moves to the endodermis where it forms a complex with SCARECROW (SCR) (Cui et al, 2007). The SHR:SCR complex induces the expression of miRNA165/6, which moves into the vascular cylinder and targets the class III HD-ZIP transcription factors, including PHABULOSA (PHB), for degradation (Carlsbecker et al, 2010). Collectively, these HD-ZIP genes determine protoversus metaxylem identity in a dose-dependent manner, and also interfere with the hormonal patterning mechanism by restricting AHP6 expression (Carlsbecker et al, 2010).…”
Section: Introductionmentioning
confidence: 99%